Exploration of individual variability to better predict the nutrient requirements of gestating sows1. (14th October 2019) - Gaillard, Charlotte; Gauthier, Raphaël; Cloutier, Laetitia; Dourmad, Jean-Yves
Abstract: Sows often receive the same feed during gestation even though their nutrient requirements vary during gestation and among sows. The objective of this study was to report the variability in nutrient requirement among sows and during gestation, in order to develop a precision feeding approach. A data set of 2, 511 gestations reporting sow characteristics at insemination and their farrowing performance was used as an input for a Python model, adapted from InraPorc, predicting nutrient requirement during gestation. Total metabolizable energy (ME ) requirement increased with increasing litter size, gestation weeks, and parity (30.6, 33.6, and 35.5 MJ/d for parity 1, 2, and 3 and beyond, respectively, P < 0.01). Standardized ileal digestible lysine (SID Lys ) requirement per kg of diet increased from weeks 1 to 6 of gestation, remained stable from weeks 7 to 10, and increased again from week 11 until the end of gestation ( P < 0.01). Average Lys requirement increased with increasing litter size (SID Lys: 3.00, 3.27, 3.50 g/kg for small, medium and large litters, P < 0.01) and decreased when parity increased (SID Lys: 3.61, 3.17, 2.84 g/kg for parity 1, 2, and 3++, P < 0.01). Standardized total tract digestible phosphorus (STTD-P ) and total calcium (Total-Ca ) requirements markedly increased after week 9, with litter size, and decreased when parity increased (STTD-P: 1.36 vs. 1.31 g/kg for parity 1 and parity 3 and beyond; Total-Ca: 4.28 vs. 4.10 g/kg for parity 1 and parity 3 and beyond, P < 0.01). Based on empirical cumulative distribution functions, a 4-diets strategy, varying in SID Lys and STTD-P content according to parity and gestation period (P1 from weeks 0 to 11, P2 from weeks 12 to 17), may be put forward to meet the requirements of 90% of the sows (2 diets for multiparous sows: P1: 2.8 g SID Lys/kg and 1.1 g STTD-P/kg; P2: 4.5 g SID Lys/kg and 2.3 g STTD-P/kg; and 2 diets for primiparous sows: P1: 3.4 g SID Lys/kg and 1.1g STTD-P/kg; P2: 5.0 g SID Lys/kg, 2.2 g STTD-P/kg). Better considering the high variability of sow requirement should thus make it possible to optimize their performance whilst reducing feeding cost and excretion. Feeding sows closer to their requirement may initially be achieved by grouping and feeding sows according to gestation week and parity, and ultimately by feeding sows individually using a smart feeder allowing the mixing of different feeds differing in their nutrient content.